The Last One among the 20th Century Priests – Folklore Collectors - Kadžytė, Gražina (Tautosakos darbai, 2016)
Rich collections of the Lithuanian Folklore Archives, now amassing over 2 million pieces, are the result of ceaseless efforts not only by the researchers, but also by numerous volunteer assistants, among which there were quite a number of enlightened Lithuanian priests. Priest Antanas Valantinas (1916–2004), an active collector of folklore from the second half of the 20th century, also belonged to this group. His 100th anniversary was celebrated this year. In 1958–1989, responding to the invitation of his contemporary folklorists to join in the work of folklore collecting, this priest recorded and handed over to the Archives 115 folklore collections, comprising in total 13 148 folklore pieces. Valantinas collected folklore both in his native places and in the parishes where he worked as a priest. Valantinas was also a literary man: he composed poems and personally published over 20 books and brochures containing poetry, essays, sermons, as well as several small folklore collections. Although the Archives still receives folklore recorded by the priests working in the second half of the previous century, Valantinas stands out among them as the most prolific collector and the last priest – folklore collector of such scope. This essay discusses the events organized to commemorate the merits of this deserving worker in the field of the Lithuanian folklore.
Keywords: -